Pregnancy in patients after valve replacement. Issue 11 (November 1976) - Oakley, C; Doherty, P
Abstract : This report is based on information obtained from a questionnaire sent to major cardiac centres in the United Kingdom. This produced details of 39 pregnancies in 34 patients after valve replacement. The 39 pregnancies gave rise to 30 healthy babies. The small size of the series probably reflects both the increasing rarity of young women with rheumatic heart disease in this country and the cautious attitude of their cardiologists. This makes it likely that these women represented the best end of the spectrum of cardiac function after valve replacement. Twenty-four pregnancies in 20 women who were not given anticoagulants producted 23 healthy babies and 1 spontaneous abortion. This group comprised 6 patients with free aortic homografts, 1 patient with a fascia lata mitral valve, 1 with a Beall tricuspid prosthesis, 1 with a combined mitral homograft and Starr Edwards aortic prosthesis, and 1 with mitral and aortic frame-mounted fascia lata valves. There were no maternal deaths or thromboembolic complications in this group which included 5 patients who were in atrial fibrillation. Fifteen pregnancies in 14 women who received anticoagulants gave rise to 7 healthy babies. The fetal losses were one stillbirth, one intrauterine death at 34 weeks, and 3 spontaneous abortions; one surviving child has hydrocephalus as a result of blood clot and there were 2 maternal deaths. This group included 13 patients with Starr Edwards valves, 11 mitral and 2 aortic. A patient with a Hammersmith mitral valve was the only one to have been treated with heparin and her valve thrombosed. One patient with a mounted mitral homograft had a cerebral embolus. Nine of these patients were in atrial fibrillation. In 3 additional patients the valve replacement was carried out during pregnancy. Two of the patients survived operation. In one of these who was treated with warfarin the pregnancy well, but there is an increased fetal wastage in patients pregnancy gave rise to a congenitally malformed baby who died in the neonatal period. The baby born to the mother who did not receive anticoagulants has a hare-lip and talipes. Women with artificial valves can tolerate the haemodynamic load of pregnancy well, but there is an increased fetal wastage in patients taking oral anticoagulants. This is probably largely attributable to fetal haemorrhage but there is also a risk of malformation caused by a teratogenic effect of warfarin. Experience gained in non-pregnant patients suggests that withholding anticoagulatns in pregnant patients with prosthetic valves would usually be undersirable but warfarin should be avoided. The advantages of biological valves were apparent in this series.